2006
DOI: 10.1139/g06-122
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of seed and berry weight in grapevine

Abstract: Fruit size and seedlessness are highly relevant traits in many fruit crop species, and both are primary targets of breeding programs for table grapes. In this work we performed a quantitative genetic analysis of size and seedlessness in an F1 segregating population derived from the cross between a classical seeded (Vitis vinifera L. 'Dominga') and a newly bred seedless ('Autumn Seedless') cultivar. Fruit size was scored as berry weight (BW), and for seedlessness we considered both seed fresh weight (SFW) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
139
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(162 citation statements)
references
References 36 publications
18
139
3
2
Order By: Relevance
“…On the contrary, the observed phenotypic cor-QTL analysis in table grapes relation between véraison time and seedleeness traits was not supported at the molecular level, which may indicate that genes controlling the 2 traits function independently of each other, but further confirmation is needed. Cabezas et al (2006) and Mejía et al (2007) found major QTL for seed number across LG 18 in different years. This QTL was associated with a pleiotropic effect on berry size or weight and ripening date, and it was not possible to dissociate seedlessness and small berry size.…”
Section: Genetic Dissectionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary, the observed phenotypic cor-QTL analysis in table grapes relation between véraison time and seedleeness traits was not supported at the molecular level, which may indicate that genes controlling the 2 traits function independently of each other, but further confirmation is needed. Cabezas et al (2006) and Mejía et al (2007) found major QTL for seed number across LG 18 in different years. This QTL was associated with a pleiotropic effect on berry size or weight and ripening date, and it was not possible to dissociate seedlessness and small berry size.…”
Section: Genetic Dissectionmentioning
confidence: 95%
“…Mejía et al (2007) found that the existence of a major QTL for stenospermocarpic seedlessness was confirmed in a specific linkage group (LG) in a segregating population of table grapes, derived from a cross of Ruby Seedless x Thompson Seedless, where this QTL was associated with pleiotropic effect on berry size or weight and on ripening date, and it was not possible to dissociate seedlessness and small berry size. Cabezas et al (2006) conducted a genetic analysis of seed and berry weight in grapevine, and they detected 12 QTL responsible for the variation in seedlessness and berry weight in the 'Dominga' x 'Autumn Seedless' F 1 progeny. Among them, 2 linked regions on LG 18 showed effects on all 3 traits considered, namely berry weight, seed number and seed fresh weight, with one of them having a major effect on QTL.…”
Section: Introductionmentioning
confidence: 99%
“…For Chromosome 18 the segregation of alleles could easily be defined with five SSR markers. We only find relevance for OIV 94 but other papers show influence in berry weight or size [23] and dependance on the population resistance against Plasmopara [11] or Erysiphe [26].…”
Section: Population 1929 (Grüner Veltliner X Malverina)mentioning
confidence: 79%
“…One hypothesis postulated the presence of a dominant allele at a single locus, later named SDI for "seed development inhibitor" (Lahogue et al 1998), inhibiting the development of the seed by regulating several recessive genes (Bouquet and Danglot 1996). The existence of this locus has been confirmed by QTL mapping (Cabezas et al 2006;Costantini et al 2008;Doligez et al 2002;Mejía et al 2007). These studies demonstrated that Sultanina-derived seedlessness is mainly regulated by SDI, which is responsible for between 50% and 90% of total phenotypic variance for this trait, depending on the mapping population and trait evaluation.…”
Section: Introductionmentioning
confidence: 85%
“…During the last two decades, there has been considerable progress in the development of molecular markers in grape. They have been used in quantitative trait loci (QTL) mapping for berry quality traits (Cabezas et al 2006;Costantini et al 2007Costantini et al , 2008Doligez et al 2002Doligez et al , 2006Doligez et al , 2010Fanizza et al 2005;Fischer et al 2004;Fournier-Level et al 2009;Mejía et al 2007) or disease resistance Lowe and Walker 2006;Marguerit et al 2009;Pauquet et al 2001;Riaz et al 2010;Welter et al 2007;Xu et al 2008;Zhang et al 2009). As a result, molecular markers closely linked to major loci responsible for important traits in table grape breeding are currently available.…”
Section: Introductionmentioning
confidence: 99%